Artificial Intelligence in Pharmaceutical Research - Mane , Sanvidha A.; Bakal , Ravindra L.; Hatwar , Pooja R. (Journal of Drug Delivery and Therapeutics, 2025)
Artificial intelligence (AI) is transforming the pharmaceutical industry by accelerating medication development and discovery. AI technologies, including machine learning and deep learning, are being applied in various areas, such as drug design, target discovery, preclinical research, and personalized medicine. AI can analyze vast amounts of data, identify patterns, and make predictions, thereby improving the efficiency and effectiveness of the drug development process. This review highlights the applications of AI in pharmaceutical research, including drug discovery, target identification, and preclinical research. We also discuss the challenges associated with AI in pharmaceutical research, such as data quality and integration, regulatory frameworks, and the need for skilled professionals. Also, the future directions of AI in pharmaceuticals, including the potential for AI to revolutionize personalized medicine and improve patient outcomes. Overall, AI has the potential to revolutionize the pharmaceutical industry by streamlining the drug development process, improving patient outcomes, and reducing costs. Keywords: Artificial Intelligence, Machine Learning, Drug Discovery, Personalized Medicine, Target Discovery.